Enhancement of tensile strength of oil palm mesocarp fiber/poly(butylene succinate) biocomposite via superheated steam-alkali treatment of oil palm mesocarp fiber / Yoon Yee Then ... [et al.] - Yoon, Yee Then; Ibrahim, NorAzowa; Zainuddin, Norhazlin; Ariffin, Hidayah; Wan Yunus, Wan MdZin (Research Management Institute (RMI), 2014)
Natural fiber is incompatible with hydrophobic polymer due to its hydrophilic nature. Therefore, surface modification of fiber is needed to impart compatibility. In this work,superheated steam (SHS)-alkali was introduced as novel surface treatment method to modify oil palm mesocarp fiber (OPMF) for fabrication of biocomposites. The OPMF was first pre-treated with SHS and subsequently treated with varying NaOH concentration (1, 2, 3, 4 and 5%) and soaking time (1, 2, 3 and 4h) at room temperature. The biocomposites were then fabricated by melt blending of 70 wt% SHS-alkali treated-OPMFs and 30 wt% poly(butylene succinate) in a Brabender internal mixer followed by hot-pressed moulding. The combination treatment resulted in fiber with rough surface as well as led to the exposure ofmicrofibers. The tensile test result showed that fiber treated at 2% NaOH solution and 3h soaking time produced biocomposite with highest improvement in tensile strength (69%) and elongation at break (36%) in comparison to that of untreated OPMF.